Krisestyring: Reformer- og besparelsesstrategier - Hansen, Hanne Foss; Kristiansen, Mads (Politik, 2012)
Denmark has been hit harder by the global nancial, economic and scal crisis than our neighbouring countries. is has meant political and administrative challenges. e crisis has been responded upon by the use of several crisis management strategies. Initiatives trying to stimulate the economy, such as advancing investments and reducing taxes, have gone hand in hand with retrenchment initiatives such as reductions in welfare programmes and cutbacks in central government. In the article a typology of crisis management strategies is developed and crisis management strategies used are analysed. In addi- tion it is discussed whether reform capacity is rebuild and elevated as well as which the e ects may be for the development of administrative policy in future.